Handbook of global contemporary Christianity : themes and developments in culture, politics, and society - Hunt, Stephen, 1954- (Brill Handbooks on Contemporary Religion, 2015)
The Handbook of Global Contemporary Christianity: Themes and Developments in Culture, Politics, and Society maps the transformations, as well as the continuities, of the largest of the major religions - engaging with the critical global issues which relate to the faith in a fast changing world. International experts in the area offer contributions focusing on global movements; regional trends and developments; Christianity, the state, politics and polity; and Christianity and social diversity. Collectively the contributors provide a comprehensive treatment of health of the religion as Christianity enters its third millennium in existence and details the challenges and dilemmas facing its various expressions, both old and new. The volume is a companion to the Handbook of Contemporary Global Christianity: Movements, Institutions, and Allegiance .